Study of particles transport along second and third generation of human airways using CFD - Mohd Qhairul, Mohd Bokhari (2010)
This thesis deals with simulation of particles transport along human airways to predict the particles deposition pattern with different inhalation flow rate and particles size. Realistic human airways model base on study by Kleinstreuer et al. (2007) was been used. The simulation has been done by two different Reynolds numbers with laminar and turbulent flow. Commercial CFD software, ANSYS FLUENT 12.1 was used. = 1883 ( = 20 ) and = 4710 ( = 50 ) are used for boundary condition. Laminar model was used for laminar flow and k-ω turbulent model was used for turbulent flow in the simulation. The results of this thesis show that flow behavior of both micro- and nano- particles vary measurably. However the deposition patterns are much more uniform for nano particle.